Structural investigation of perfluorocarboxylic acid derivatives formed in the reaction with N, N-dimethylformamide dialkylacetals. Issue 2 (April 2020) - Stróżyńska, Monika; H. Gross, Jürgen; Schuhen, Katrin
A structural investigation of perfluorocarboxylic acid derivatives formed in the reaction with N, N-dimethylformamide dialkylacetals employing several techniques of mass spectrometry (MS) is described. Two derivatizing reagents, dimethylformamide dimethyl acetal (DMF-DMA) and dimethylformamide diethylacetal (DMF-DEA) were used. In contrast to carboxylic acids, perfluorocarboxylic acids are not able to form alkyl esters as the main product in this reaction. We found that perfluorooctanoic acid (PFOA) forms a salt with N, N-dimethylformamide dialkylacetals. This salt undergoes a further reaction inside the injection block of a gas chromatograph (GC) by loss of CO2 and then forms 1, 1-perfluorooctane-(N, N, N, N-tetramethyl)-diamine. The GC-MS experiments using both electron ionization (EI) and positive-ion chemical ionization (PCI) revealed that the same reaction products are formed with either derivatizing reagent. Subjecting the perfluorocarboxylic acid derivative to electrospray ionization (ESI) and direct analysis in real time (DART), both positive- and negative-ion modes indicated that cluster ions are formed. In the positive-ion mode, this cluster ion consists of two iminium cations and one PFOA anion, while in the negative-ion mode, it comprises two PFOA anions and one cation. The salt structure was further confirmed by liquid injection field desorption/ionization (LIFDI) as well as infrared (IR) spectroscopy. We propose a simple mechanism of N, N, N′, N′-tetramethylformamidinium cation formation. The structure elucidation is supported by specific fragment ions as obtained by GC-EI-MS and GC-PCI-MS analyses.